Transition for transduction: how to make cardiac endothelial cells more permissive to AAV. (10th June 2022) - Volf, N; Ring, N; Colliva, A; Vuerich, R; Braga, L; Zentilin, L; Zacchigna, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Despite major attempts aiming to revascularize an ischemic heart, prognosis of cardiac ischemia remains poor. A major obstacle for the induction of new blood vessels, referred as therapeutic angiogenesis, is inefficient gene transfer in cardiac endothelial cells (ECs). This poor permissiveness to genetic modification is a limiting step in studies of pathological conditions with inadequate, but also with increased vascularization. To study the function of a specific gene and its potential implications in angiogenesis, the most straightforward approach would be to either overexpress or silence it in ECs. We and others have tested multiple protocols for either transfection and transduction of primary ECs in vitro and in vivo, with no success. Vectors based on Adeno-associated virus (AAV) and Lentivirus (LV) stand as ideal tools for gene delivery, however they do not work in cardiac ECs. Purpose: To enhance the permissiveness of EC, we optimized and performed high-throughput screening on adult cardiac ECs using a library of FDA approved drugs, to search for compounds increasing transduction by AAV6 and LV, with the final aim to identify the major determinants inhibiting genetic modification of ECs. Methods: Cardiac ECs were isolated from 2 months old C57BL/6 mice and plated on 384-well plates. After 48 hours, the FDA drug library (> 1500 compounds) was added together with AAV6-dsRed and LV-GFP. Cells were fixed with 4% PFA 72 hours post-transduction, and subsequently stained for the EC marker ERG. The levels of AAV6-dsRed, LV-GFP and ERG expression were assessed by automated, high-content microscopy. Results: After two rounds of screening at different drug concentrations, we obtained a list of candidate compounds able to increase adult cardiac EC transduction by either AAV6 or LV over two folds. Among these, our best hit increasing AAV6-mediated transduction was Vatalanib, a tyrosine kinase inhibitor acting on VEGFRs, PDGFR, and c-Kit. Valatanib not only increased permissiveness to AAV6, but it also changed the morphology of the cells, which became elongated and similar to mesenchymal cells. This suggested ongoing endothelial mesenchymal transition (EndMT), which was verified by decreased CD31 and increased α-SMA expression. Interestingly, AAV mostly transduced cells with the lowest CD31 expression. Conclusions: Our high-throughput screening identified Vatalanib as the most potent drug in increasing permissiveness of cardiac ECs to AAV transduction. Because the drug induced loss of CD31 and gain in α-SMA, we hypothesized that the reason for increased permissiveness was EndMT. This hypothesis is consistent with the known mechanism of action of Valatanib, which inhibits VEGFR2 and thus interferes with VEGF signalling, that in turn is essential to maintain EC identity.